Pengaruh City Branding dan City Image Terhadap Keputusan Berkunjung Wisatawan ke Kota Denpasar - Prabainastu, Harsacitta (JURNAL DESTINASI PARIWISATA; Vol 8 No 2 (2020): VOL 8, NO 2 (2020): (JULY-DECEMBER) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2020.v08.i02.p03, 2020)
One of the city that developing in increasing tourist visits is Denpasar. In increasing number of visits, one of the ways that government had to do is city branding. In this research city branding is influenced by city image, city branding influences visit decision, and city image influences visit decision. This research method uses qualitative approach with data collection techniques in qualitative and literature review. Findings of this research indicate that city branding has significant effect on city image, city branding has significant effect on visit decision and city image has significant effect on visit decision. Even though, there is relative answer, but the government of Denpasar city must realize this condition to develop Denpasar city with sustainable heritage tourism. Key words : city branding, city image